De novo assembly and analysis of RNA-seq data - Robertson, G.; Schein, J.; Chiu, R.; Corbett, R.; Field, M.; Jackman, S.; Mungall, K.; Lee, S.; Okada, H.; Qian, J.; Griffith, M.; Raymond, A.; et al. (2010)
We describe Trans-ABySS, a de novo short-read transcriptome assembly and analysis pipeline that addresses variation in local read densities by assembling read substrings with varying stringencies and then merging the resulting contigs before analysis. Analyzing 7.4 gigabases of 50-base-pair paired-end Illumina reads from an adult mouse liver poly(A) RNA library, we identified known, new and alternative structures in expressed transcripts, and achieved high sensitivity and specificity relative to reference-based assembly methods. © 2010 Nature America, Inc. All rights reserved.